The Relationship between Parents’ Knowledge and Behaviors with The Acute Respiratory Infection Incidence of Children Under Five in Tangerang - Sari, Ervi Novita; Tinambunan, Eva Sri Lestari; Prameswari, Gita; Kartika, Lia; Tahapary, Prisca Adi (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The purpose of the study was to obtain the relationship between the parents’ knowledge and behaviours towards the ARI incidence in children under five years. This research used a descriptive quantitative methods The population was parents who have children under five years in one sub-district in Tangerang. 180 samples were taken using total sampling technique. The data collection was collected online with a valid and reliable questionnaire. Univariate test results showed 94 respondents (52.2%) had a high level of knowledge, and 131 respondents (72.8%) had good behaviours. There was a significant relationship between parent’s knowledge with ARI incidence (p=0.007). There was also a significant relationship between parents’ behavior with ARI incidence (p=0.038). Nurses must be actively providing health education related to ARI to parents and follow up regularly. Further research can develop regarding the factors that influence the knowledge and behavior of parents of ARI in children under five years